2007
DOI: 10.4103/1596-3519.55722
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum lipid profile of under-five Nigerian children

Abstract: Background: Serum lipid profile assay forms one of the special investigations in most chemical pathology laboratories worldwide. Several studies in children from different countries have shown that serum lipids exhibit age and geographical pattern of variation prior to puberty. This study was conducted to evaluate serum lipid profile in Nigerian children aged 6 to 36 months. Methods: A total of 115 randomly selected apparently healthy children were studied. These consisted of 38, 40 and 37 children in groups I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…Lipid profile became a useful parameter through its use in the diagnosis of several cardiovascular diseases and control of diabetic patients [9]. The results of our study showed a significant increase in TC (+36.4%), TG (+44.9%) and LDL-C (+53.37%) associated with a remarkable decrease in HDL-C (-15.16%) in diabetic rats.…”
Section: Glycemia and Lipid Profilesupporting
confidence: 50%
“…Lipid profile became a useful parameter through its use in the diagnosis of several cardiovascular diseases and control of diabetic patients [9]. The results of our study showed a significant increase in TC (+36.4%), TG (+44.9%) and LDL-C (+53.37%) associated with a remarkable decrease in HDL-C (-15.16%) in diabetic rats.…”
Section: Glycemia and Lipid Profilesupporting
confidence: 50%
“…Data on normal lipid profiles in children <2 years of age are lacking. Children in the US may have higher cholesterol levels than children in Africa (20). Genetic, environmental, and dietary factors likely play a role in lipid metabolism and it is unclear whether US standards are applicable for monitoring HIV- and HAART-associated dyslipidemia in African infants.…”
mentioning
confidence: 99%
“…Lipid profile is of crucial importance in the diagnosis and treatment of several cardiovascular diseases and control of diabetic patients [23]. Studies have reported that cardiovascular complications associated with diabetes are due to disturbances of lipid metabolism [24].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the production of ROS and lipid peroxidation are increased in diabetic patients and that oxidative stress is responsible for the pathophysiology of diabetes [23], especially, that associated with antioxidant treatment showed significant improvement and prevention against cardiovascular complications [25].…”
Section: Discussionmentioning
confidence: 99%